dd-DISTANCE IN SOME CORONA RELATED GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
Let G = (V, E) be a simple graph. Let u, v be two vertices of a connectedgraph G. Then the d-length of a u-v path defined as dd(u, v) = d(u, v) + deg(u) + deg(v) +deg(u) deg(v), where d(u, v) is the shortest distance between the vertices u and v. In thispaper dd – distance of some corona relaed graphs are determined.